Research methods in linguistic anthropology - Perrino, Sabina M.; Pritzker, Sonya E. (London, UK Bloomsbury Academic, 2022)
"For research in linguistic anthropology, the successful design and execution of research projects is a challenging but essential task. Balancing research design with data collection methods, this is the first textbook to guide readers through the key issues and principles of the core research methods in linguistic anthropology. Designed for students conducting research projects for the first time, or for researchers in need of a primer on key methodologies, this book provides clear introductions to key concepts, accessible discussions of theory and practice through illustrative examples, and critical engagement with current debates. Topics covered include creating and refining research questions; planning research projects; ethical considerations for research; quantitative and qualitative data collection methods; data processing; analysing and presenting research data; and how to write a successful grant application. Each chapter is further illustrated by cases studies which showcase methods in practice, and are supported by a range of pedagogical tools, including activities and exercises, discussion questions, and further reading lists. Research Methods in Linguistic Anthropology is an essential resource for both experienced and novice linguistic anthropologists and is a valuable textbook for research methods courses"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Anthropological linguistics -- Research -- Methodology